Violence – essence and forms of manifestation - Uzunov, Stoyan (Law Journal of New Bulgarian University, 2022)
Violence has accompanied human development from ancient times to the present days. It is pervasive and multifaceted. As a social phenomenon, it has been the subject of diverse studies aimed at explaining its essence. It is most often seen as the result of an individual’s aggressive behavior directed at another individual. Violence has different forms of manifestation – from different types of mental harassment to physical abuse, which can turn into a crime. Depending on the specific relationships that develop between people, violence most often occurs in the family environment, in the school and in the work environment.